2021
DOI: 10.3389/fpubh.2020.582701
|View full text |Cite
|
Sign up to set email alerts
|

Population-Level Preparedness About Preventive Practices Against Coronavirus Disease 2019: A Cross-Sectional Study Among Adults in Bangladesh

Abstract: This study assessed the preparedness regarding the preventive practices toward the coronavirus disease 2019 (COVID-19) among the adult population in Bangladesh. Data were collected through an online survey with a sample size of 1,056. We constructed four variables (individual, household, economic, and community and social distancing) related to preparedness based on the principal component analysis of eight items. We employed descriptive statistics and multiple linear regression analysis. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
7
7
0
Order By: Relevance
“…Females showed significantly higher levels of preparedness than males, which can decrease the risk of infection. Women’s higher perception and better compliance regarding COVID-19 related preparedness were also found in other studies [ 10 , 23 ]. Besides, females were more likely to have better knowledge, a favourable attitude, and good practice behaviours [ 24 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Females showed significantly higher levels of preparedness than males, which can decrease the risk of infection. Women’s higher perception and better compliance regarding COVID-19 related preparedness were also found in other studies [ 10 , 23 ]. Besides, females were more likely to have better knowledge, a favourable attitude, and good practice behaviours [ 24 ].…”
Section: Discussionsupporting
confidence: 79%
“…A favourable attitude towards COVID-19 was found to influence preparedness skills positively. This has been supported by another study in Bangladesh [ 23 ]. There is also a significant positive association between attitude and practice of precaution measures [ 17 , 20 ].…”
Section: Discussionsupporting
confidence: 73%
“…Bangladesh has used nontherapeutic measures to reduce the numbers of COVID-19 confirmed cases in the absence of vaccine and treatment. [4][5][6] However, due to higher population density, unplanned urbanization, and diverse socioeconomic conditions, these measures were not as effective as hoped for. The population density was the most crucial predictor of infection rates.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the numbers of COVID-19 confirmed cases and flatten the curve of the infection in the absence of a vaccine and explicit treatment, Bangladesh has taken nontherapeutic measures, including full (or partial lockdown), risk zone-based lockdowns, maintaining social isolation, limiting working hours, closing all institutions, restaurants and, shopping malls, and restricting the movement of people through travel bans. [4][5][6] However, these preventive measures may not have been as effective as they have been in other countries due to higher population density and diverse socioeconomic conditions. In urban areas, where there are a higher population density and connectivity, there is a great risk of spreading the virus.…”
Section: Introductionmentioning
confidence: 99%
“…It also increases the risk of secondary transmission within the household (Shah et al, 2020). Whilst some studies have reported a reluctance amongst the general public to engage in preventative practices in Bangladesh at the individual level (Hossain et al, 2021;Ferdous et al, 2020), little is known about the role of families in adopting preventative practices within the context of the COVID-19 pandemic in the country.…”
Section: Introductionmentioning
confidence: 99%